High wear resistant fluorine-free medical grade nylon composite material and preparation method thereof

CN123004128APending Publication Date: 2026-10-30SUZHOU UNIKING NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611422521.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

液态有机硅能够降低接触界面的剪切阻力,但直接加入尼龙熔体时容易在高温剪切和冷却过程中形成局部富集相;二氧化硅等硬质颗粒能够提高承载能力,但颗粒与尼龙基体界面结合不足时,在反复摩擦过程中可能发生颗粒拔出,脱落颗粒进入摩擦副后又会形成第三体磨粒

Benefits of technology

本发明首先将液态有机硅阻燃剂FCA-117由最终复合时的自由加入状态转变为介孔二氧化硅孔道及表面凹陷中的受限分布状态,并通过正硅酸乙酯水解缩合形成孔口限域结构,再以OFS-6040硅烷调节颗粒外表面,由此形成“孔道负载—孔口限域—外表面处理”的连续功能结构。孔口限域结构的作用是降低FCA-117的快速外迁而非将其完全封闭;摩擦过程中,孔口及近表面区域的FCA-117仍可参与接触界面的剪切调控,因此能够在保留减摩作用的同时减少加工、储存和热老化过程中的非必要迁移。OFS-6040外表面处理进一步提高颗粒与聚酰胺12之间的界面稳定性和抗拔出能力,使孔内功能相保持与颗粒/基体界面结合分别由不同结构层级承担。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of high polymer materials, in particular to a high-wear-resistance fluorine-free medical-grade nylon composite material and a preparation method thereof. The composite material is composed of polyamide 12 100 parts, organic silicon wear-resistant particles 2.5-5.0 parts, wear-resistant and friction-reducing functional master batch 6-12 parts, antioxidant 1098 0.20-0.40 parts and antioxidant 168 0.05-0.20 parts in terms of mass fraction. The organic silicon wear-resistant particles are prepared through negative pressure impregnation of a flame retardant FCA-117, hydrolysis and condensation of tetraethyl orthosilicate to form a pore-limiting structure and external surface treatment of OFS-6040 silane; the wear-resistant and friction-reducing functional master batch is prepared through pre-melting and compounding of polypropylene, A1401 wear-resistant agent, maleic anhydride grafted polypropylene, HPN-68L nucleating agent and antioxidant 1010. The pore-limiting structure improves the resistance of FCA-117 in the pore channel to outward migration instead of completely sealing the pore channel, and the external surface treatment of the particles and the pre-structuring of the wear-resistant and friction-reducing functional master batch make the composite material have the advantages of low friction and wear, less wear debris, low surface migration and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, specifically to a high-wear-resistant, fluorine-free medical-grade nylon composite material and its preparation method. Background Technology

[0002] Engineering plastic components in medical devices may experience continuous sliding contact or repeated friction during assembly, opening and closing, transmission, positioning, clamping, or reciprocating motion. For such components, in addition to meeting basic mechanical properties and processing stability requirements, it is also necessary to consider a low coefficient of friction, minimal wear, minimal wear debris, and a relatively stable surface condition. With prolonged use, if lubricating or processing components migrate, accumulate, or precipitate within the material, it can easily cause a difference between the initial frictional properties and long-term performance, and increase surface particles and wiping material.

[0003] Current friction-reducing and wear-resistant modifications of nylon materials typically employ low surface energy lubricating components, polymeric tribological modifiers, or inorganic wear-resistant particles. Liquid silicone can reduce shear resistance at the contact interface, but when directly added to nylon melt, it easily forms locally enriched phases during high-temperature shearing and cooling. Hard particles such as silica can improve load-bearing capacity, but if the bonding between the particles and the nylon matrix is ​​insufficient, particles may be pulled out during repeated friction. These detached particles then enter the friction pair and form third-body abrasive particles. Therefore, simply blending low-shear components and hard particles is insufficient to stably achieve a balance between low friction, low wear, and low migration.

[0004] On the other hand, polymeric wear-resistant agents and low-friction polyolefin phases can reduce dependence on free-migrating low-molecular-weight lubrication methods, but there are polarities and interfacial compatibility differences between polyolefins and polyamides. If polypropylene, polymeric wear-resistant agents, compatibility components, and nucleating agents are added directly to the polyamide melt as independent raw materials, the distribution positions of each functional component in the high-shear system are highly random, which is not conducive to establishing a stable low-friction dispersed phase and is also prone to interfacial peeling and dispersion coarsening.

[0005] Therefore, it is necessary to construct a wear-resistant modification system that pre-constructs key functional structures before entering the nylon matrix, so that the low-shear organosilicon component, inorganic load-bearing particles, and polyolefin wear-resistant and friction-reducing phase can form relatively stable functional units, and obtain a composite material with stable performance by direct mixing and one-time melt extrusion in the final composite stage. Summary of the Invention

[0006] In view of this, the purpose of the present invention is to provide a high wear-resistant, fluorine-free medical-grade nylon composite material and its preparation method.

[0007] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a high wear-resistant, fluorine-free medical-grade nylon composite material, which, by mass parts, consists of 12,100 parts of polyamide, 2.5-5.0 parts of organosilicon wear-resistant particles, 6-12 parts of wear-resistant and friction-reducing functional masterbatch, 0.20-0.40 parts of antioxidant 1098 and 0.05-0.20 parts of antioxidant 168.

[0008] Further, the organosilicon wear-resistant particles are prepared by the following method: mesoporous silica is placed in a negative pressure environment to expel the gas inside the pores; flame retardant FCA-117 is preheated to obtain organosilicon impregnation material; under the condition of maintaining negative pressure, the organosilicon impregnation material is added to mesoporous silica, and after negative pressure wetting, restoration to normal pressure and mixing, organosilicon impregnation particles are obtained; tetraethyl orthosilicate is added to an aqueous ethanol solution and pre-hydrolyzed to obtain silica sol; organosilicon impregnation particles are added to silica sol, and after dispersion, condensation reaction, filtration and drying, pore-confined particles are obtained; OFS-6040 silane is added to an aqueous ethanol solution for pre-hydrolyzation to obtain silane treatment solution; pore-confined particles are added to silane treatment solution, and after dispersion, heat preservation reaction, filtration, drying and sieving, organosilicon wear-resistant particles are obtained.

[0009] Furthermore, the raw materials for the self-preparation of the organosilicon wear-resistant particles include, by mass parts: 100 parts mesoporous silica, 8-15 parts flame retardant FCA-117, 4-8 parts tetraethyl orthosilicate, and 2-5 parts OFS-6040 silane.

[0010] Furthermore, during the preparation of the organosilicon wear-resistant particles, mesoporous silica is evacuated to -0.065 to -0.090 MPa at 50-65°C and maintained for 10-20 min; flame retardant FCA-117 is added after preheating to 50-65°C, and the negative pressure is maintained for 5-15 min, followed by restoring to normal pressure within 1-3 min and mixing for 20-40 min.

[0011] Furthermore, the tetraethyl orthosilicate is pre-hydrolyzed at 25-35°C for 30-60 min; the organosilicon-impregnated particles are added to the silica sol and then subjected to a condensation reaction at 40-60°C for 40-90 min.

[0012] Furthermore, the OFS-6040 silane is pre-hydrolyzed for 20-40 minutes at a pH of 4.5-5.2; after the pore-confined particles are added to the silane treatment solution, the reaction is carried out at 55-70°C for 60-100 minutes.

[0013] Furthermore, in the ethanol-water solution used for the pre-hydrolysis of tetraethyl orthosilicate and the pre-hydrolysis of OFS-6040 silane, the mass fraction of ethanol is 82%-90%, and the remainder is water; the mass fraction of ethanol is expressed as the percentage of the mass of ethanol to the total mass of ethanol and water.

[0014] Furthermore, the flame retardant FCA-117 is added under negative pressure after the gas in the mesoporous silica is expelled from the pores. It enters the pores and surface depressions through negative pressure wetting, the pressure difference generated by restoring normal pressure, and capillary action within the pores. After the tetraethyl orthosilicate is pre-hydrolyzed to form a silica sol, it condenses on the outer surface of the organosilicon-impregnated particles and in the pore area, forming an inorganic pore-confined structure. This pore-confined structure reduces the rapid outward migration of FCA-117 within the pores during processing, storage, and thermal aging by narrowing the effective migration channels and increasing mass transfer resistance. This structure does not completely seal the pores; FCA-117 at the pore openings and near the particle surface can still participate in interface regulation during frictional contact.

[0015] Further, the wear-resistant and friction-reducing functional masterbatch is prepared by the following method: polypropylene, A1401 wear-resistant agent, maleic anhydride-grafted polypropylene, HPN-68L nucleating agent and antioxidant 1010 are mixed to obtain masterbatch premix; the masterbatch premix is ​​melt-extruded, cooled and pelletized and dried to obtain wear-resistant and friction-reducing functional masterbatch.

[0016] Furthermore, the raw materials for the preparation of the wear-resistant and friction-reducing functional masterbatch include, by mass parts: 100 parts polypropylene, 25-40 parts A1401 wear-resistant agent, 15-25 parts maleic anhydride-grafted polypropylene, 0.20-0.50 parts HPN-68L nucleating agent, and 0.10-0.30 parts antioxidant 1010.

[0017] Furthermore, during the preparation of the wear-resistant and friction-reducing masterbatch, the melt extrusion temperature is 170-205℃; in a specific embodiment, the twin-screw extruder can adopt zoned temperature control, and the screw speed is matched according to the length-to-diameter ratio of the equipment and the feed rate; after the extruded material is cooled, it is granulated, and the particle size is preferably 3.0-4.0mm.

[0018] Secondly, the present invention provides a method for preparing the above-mentioned high wear-resistant, fluorine-free medical-grade nylon composite material, comprising the following preparation steps: Polyamide 12, silicone wear-resistant particles, wear-resistant and friction-reducing functional masterbatch, antioxidant 1098 and antioxidant 168 are mixed to obtain a composite premix; the composite premix is ​​melt-extruded, cooled and pelletized and dried to obtain a high wear-resistant fluorine-free medical-grade nylon composite material.

[0019] Furthermore, the temperature of the composite premixed material melt extrusion is 190-230℃. In a specific embodiment, the twin-screw extruder can adopt zoned temperature control, and the screw speed can be adjusted according to the melt conveying and dispersion state; after cooling, the extruded material is pelletized, and the particle size is preferably 3.0-4.0mm.

[0020] Furthermore, the polyamide 12 is dried before final mixing; the final composite material, after pelleting, is preferably vacuum dried at 65-80°C and a vacuum degree of -0.075 to -0.095 MPa for 4-8 hours. These drying conditions are used to reduce the moisture content of the pellets and do not constitute a necessary limitation on the scope of the claims.

[0021] The beneficial effects of this invention are: This invention first transforms the liquid organosilicon flame retardant FCA-117 from its freely added state during final compounding into a confined distribution state within mesoporous silica channels and surface depressions. A pore-confined structure is then formed through the hydrolysis and condensation of tetraethyl orthosilicate. Finally, OFS-6040 silane is used to adjust the outer surface of the particles, thereby creating a continuous functional structure of "pore loading—pore confinement—outer surface treatment." The pore-confined structure reduces the rapid migration of FCA-117 rather than completely sealing it. During friction, FCA-117 in the pore and near-surface regions can still participate in the shear regulation of the contact interface, thus reducing unnecessary migration during processing, storage, and thermal aging while retaining its anti-friction effect. The OFS-6040 outer surface treatment further improves the interfacial stability and pull-out resistance between the particles and polyamide 12, ensuring that the functional phase within the pores remains bonded to the particle / matrix interface at different structural levels.

[0022] This invention pre-melts and composites polypropylene, A1401 wear-resistant agent, maleic anhydride-grafted polypropylene, and HPN-68L nucleating agent into a wear-resistant and friction-reducing functional masterbatch, allowing the low-friction polyolefin phase, wear-resistant agent, and compatible components to be pre-constructed before entering polyamide 12. Compared to adding each component directly to the polyamide melt, this method is beneficial for controlling the size and interfacial bonding of the low-friction dispersed phase, reducing the coarsening and peeling of the dispersed phase and the resulting wear debris during friction.

[0023] This invention directly mixes two types of pre-constructed functional units with polyamide 12 and antioxidants, followed by a single melt extrusion process, achieving the final composite without relying on multi-stage side feeding. The organosilicon wear-resistant particles primarily construct the functional units through FCA-117 spatial confinement and particle / polyamide 12 interface stability, while the wear-resistant and friction-reducing masterbatch stabilizes the dispersion of the polyolefin phase, wear-resistant agent, and compatible components. The two types of functional units target different objects and complement each other, enabling the material to maintain mechanical properties while achieving lower friction and wear, less wear debris, and lower surface migration. This demonstrates a structural modification effect distinct from freely adding lubricating components, simply filling inorganic particles, or directly blending various wear-resistant components. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative effort are all within the scope of protection of the present invention. Unless otherwise stated, the following "parts" refers to parts by weight.

[0025] The main sources of materials used in the embodiments of this application are as follows: The polyamide 12, designated LX7229, was purchased from Shanghai Tinger Plastic Technology Co., Ltd.

[0026] The mesoporous silica has a mesh size of 2000 and was purchased from Qinghe County Chaotai Metal Materials Co., Ltd.

[0027] OFS-6040 silane was purchased from Shanghai Jiuying New Materials Co., Ltd.

[0028] The flame retardant FCA-117 is a liquid silicone flame retardant purchased from Gabette (Guangzhou) New Materials Co., Ltd.

[0029] HPN-68L nucleating agent was purchased from Shanghai Jiuying New Materials Co., Ltd.

[0030] A1401 wear-resistant agent was purchased from Shanghai Yiyushuo New Materials Co., Ltd.

[0031] Example 1

[0032] A method for preparing a high-wear-resistant, fluorine-free medical-grade nylon composite material is as follows: Preparation of organosilicon wear-resistant particles: 100 parts by mass of mesoporous silica, 8 parts of flame retardant FCA-117, 4 parts of tetraethyl orthosilicate, and 2 parts of OFS-6040 silane were taken. The mesoporous silica was dried at 110℃ for 3 hours and then placed in a vacuum mixing device. A vacuum was drawn to -0.065 MPa at 50℃ and maintained for 10 minutes to expel gas from the pores. The flame retardant FCA-117 was preheated to 50℃ to obtain an organosilicon impregnation material. The negative pressure was maintained, and the organosilicon impregnation material was added within 5 minutes. The negative pressure was maintained for another 5 minutes, then restored to normal pressure within 1 minute and mixed for 20 minutes to obtain organosilicon impregnated particles. Tetraethyl orthosilicate was added to an 82% (w / w) aqueous solution of ethanol and pre-hydrolyzed at 25℃ for 30 minutes to obtain a silica sol. The organosilicon... The impregnated particles were added to silica sol, dispersed at 40°C and subjected to a condensation reaction for 40 min. After filtration, they were dried at 80°C for 3 h to obtain pore-confined particles. OFS-6040 silane was added to an 82% ethanol aqueous solution, and the pH was adjusted to 4.5 with glacial acetic acid. The solution was pre-hydrolyzed at 25°C for 20 min to obtain a silane treatment solution. The pore-confined particles were added to the silane treatment solution, dispersed at 55°C and subjected to a heat treatment reaction for 60 min. After filtration, the solution was dried at 100°C under a vacuum of -0.080 MPa for 2 h. After cooling, the solution was passed through a 100-mesh sieve to obtain organosilicon wear-resistant particles.

[0033] Preparation of wear-resistant and friction-reducing functional masterbatch: By mass, take 100 parts of polypropylene, 25 parts of A1401 wear-resistant agent, 15 parts of maleic anhydride-grafted polypropylene, 0.20 parts of HPN-68L nucleating agent, and 0.10 parts of antioxidant 1010, mix at room temperature for 3 minutes to obtain masterbatch premix; add the masterbatch premix to a twin-screw extruder, with the temperatures from the feed section to the die head being 170℃, 180℃, 190℃, 195℃, 190℃, and 185℃ respectively, and the screw speed being 180 r / min; after melt extrusion and water cooling, pelletize, control the particle size to be 3.0-4.0 mm, and dry at 60℃ for 2 hours to obtain wear-resistant and friction-reducing functional masterbatch.

[0034] Preparation of composite material: Taking 100 parts of polyamide 12 as 100 parts, take 100 parts of polyamide 12, 2.5 parts of organosilicon wear-resistant particles, 6 parts of wear-resistant and friction-reducing functional masterbatch, 0.20 parts of antioxidant 1098 and 0.05 parts of antioxidant 168; the polyamide 12 is pre-dried at 75℃ for 8 hours; the raw materials are mixed at room temperature for 3 minutes to obtain a composite premix; the composite premix is ​​added to a twin-screw extruder, the temperature from the feed section to the die head is 190℃, 205℃, 215℃, 220℃, 215℃, 205℃ and 200℃ respectively, and the screw speed is 220 r / min; after melt extrusion, water cooling and pelleting, the particle size is controlled to be 3.0-4.0 mm, and vacuum dried at 65℃ and vacuum degree -0.080MPa for 4 hours to obtain a high wear-resistant fluorine-free medical grade nylon composite material.

[0035] Example 2

[0036] A method for preparing a high-wear-resistant, fluorine-free medical-grade nylon composite material is as follows: Preparation of organosilicon wear-resistant particles: By mass, 100 parts of mesoporous silica, 11.5 parts of flame retardant FCA-117, 6 parts of tetraethyl orthosilicate, and 3.5 parts of OFS-6040 silane were taken. The mesoporous silica was dried at 120℃ for 3 hours and then placed in a vacuum mixer. A vacuum was drawn to -0.078 MPa at 58℃ and maintained for 15 minutes. The flame retardant FCA-117 was preheated to 58℃ to obtain an organosilicon impregnating material. The negative pressure was maintained, and the organosilicon impregnating material was added within 8 minutes. The negative pressure was maintained for another 10 minutes, then restored to normal pressure within 2 minutes and mixed for 30 minutes to obtain organosilicon impregnated particles. Tetraethyl orthosilicate was added to ethanol at a mass fraction of 86%. Silica sol was obtained by pre-hydrolyzing the silicone-impregnated particles in an ethanol-water solution at 30°C for 45 min. The particles were then dispersed at 50°C and subjected to a condensation reaction for 65 min. After filtration, the particles were dried at 90°C for 3 h to obtain pore-confined particles. OFS-6040 silane was added to an 86% ethanol-water solution, and the pH was adjusted to 4.8 with glacial acetic acid. The solution was then pre-hydrolyzed at 30°C for 30 min to obtain a silane treatment solution. The pore-confined particles were added to the silane treatment solution, dispersed at 62°C, and subjected to a heat treatment reaction for 80 min. After filtration, the solution was dried at 110°C under a vacuum of -0.085 MPa for 3 h. After cooling, the solution was passed through a 100-mesh sieve to obtain organosilicon wear-resistant particles.

[0037] Preparation of wear-resistant and friction-reducing functional masterbatch: By mass, 100 parts of polypropylene, 32.5 parts of A1401 wear-resistant agent, 20 parts of maleic anhydride-grafted polypropylene, 0.35 parts of HPN-68L nucleating agent, and 0.20 parts of antioxidant 1010 were mixed at room temperature for 4 minutes to obtain masterbatch premix. The masterbatch premix was added to a twin-screw extruder, with the temperatures from the feed section to the die head being 175℃, 185℃, 195℃, 200℃, 195℃, and 190℃ respectively, and the screw speed being 230 r / min. After melt extrusion and water cooling, the particles were pelletized, with the particle size controlled at 3.0-4.0 mm, and dried at 68℃ for 3 hours to obtain wear-resistant and friction-reducing functional masterbatch.

[0038] Preparation of composite material: Taking 100 parts of polyamide 12 as the basis, take 100 parts of polyamide 12, 3.8 parts of organosilicon wear-resistant particles, 9 parts of wear-resistant and friction-reducing functional masterbatch, 0.30 parts of antioxidant 1098 and 0.12 parts of antioxidant 168; the polyamide 12 is pre-dried at 80℃ for 8h; the raw materials are mixed at room temperature for 5min to obtain composite premix; the composite premix is ​​added to a twin-screw extruder, the temperature from the feed section to the die head is 195℃, 210℃, 220℃, 225℃, 220℃, 210℃ and 205℃ respectively, and the screw speed is 270r / min; after melt extrusion, water cooling and pelleting, the particle size is controlled to be 3.0-4.0mm, and vacuum dried at 72℃ and vacuum degree -0.085MPa for 6h to obtain high wear-resistant fluorine-free medical grade nylon composite material.

[0039] Example 3

[0040] A method for preparing a high-wear-resistant, fluorine-free medical-grade nylon composite material is as follows: Preparation of organosilicon wear-resistant particles: 100 parts by mass of mesoporous silica, 15 parts by mass of flame retardant FCA-117, 8 parts by mass of tetraethyl orthosilicate, and 5 parts by mass of OFS-6040 silane were taken. The mesoporous silica was dried at 130℃ for 3 hours and then placed in a vacuum mixing device. A vacuum was drawn to -0.090 MPa at 65℃ and maintained for 20 minutes. The flame retardant FCA-117 was preheated to 65℃ to obtain an organosilicon impregnating material. The negative pressure was maintained, and the organosilicon impregnating material was added within 12 minutes. The negative pressure was maintained for another 15 minutes, then restored to normal pressure within 3 minutes and mixed for 40 minutes to obtain organosilicon impregnated particles. Tetraethyl orthosilicate was added to a solution of 90% ethanol. Silica sol was obtained by pre-hydrolyzing in an alcohol-water solution at 35°C for 60 min. Organosilicon-impregnated particles were added to the silica sol, dispersed at 60°C, and subjected to a condensation reaction for 90 min. After filtration, the particles were dried at 100°C for 3 h to obtain pore-confined particles. OFS-6040 silane was added to an ethanol-water solution with a mass fraction of 90%, and the pH was adjusted to 5.2 with glacial acetic acid. The solution was pre-hydrolyzed at 35°C for 40 min to obtain a silane treatment solution. The pore-confined particles were added to the silane treatment solution, dispersed at 70°C, and subjected to a heat treatment reaction for 100 min. After filtration, the solution was dried at 120°C under a vacuum of -0.090 MPa for 4 h. After cooling, the solution was passed through a 100-mesh sieve to obtain organosilicon wear-resistant particles.

[0041] Preparation of wear-resistant and friction-reducing functional masterbatch: By mass, take 100 parts of polypropylene, 40 parts of A1401 wear-resistant agent, 25 parts of maleic anhydride-grafted polypropylene, 0.50 parts of HPN-68L nucleating agent, and 0.30 parts of antioxidant 1010, mix at room temperature for 5 minutes to obtain masterbatch premix; add the masterbatch premix to a twin-screw extruder, with the temperatures from the feed section to the die head being 180℃, 190℃, 200℃, 205℃, 200℃, and 195℃ respectively, and the screw speed being 280 r / min; after melt extrusion and water cooling, pelletize, control the particle size to be 3.0-4.0 mm, and dry at 75℃ for 4 hours to obtain wear-resistant and friction-reducing functional masterbatch.

[0042] Preparation of composite material: Taking 100 parts of polyamide 12 as 100 parts, take 100 parts of polyamide 12, 5.0 parts of organosilicon wear-resistant particles, 12 parts of wear-resistant and friction-reducing functional masterbatch, 0.40 parts of antioxidant 1098 and 0.20 parts of antioxidant 168; the polyamide 12 is pre-dried at 85℃ for 10h; the raw materials are mixed at room temperature for 8min to obtain composite premix; the composite premix is ​​added to a twin-screw extruder, the temperature from the feed section to the die head is 200℃, 215℃, 225℃, 230℃, 225℃, 215℃ and 210℃ respectively, and the screw speed is 320r / min; after melt extrusion and water cooling, it is pelletized, the particle size is controlled to be 3.0-4.0mm, and vacuum dried at 80℃ and vacuum degree -0.090MPa for 8h to obtain high wear-resistant fluorine-free medical grade nylon composite material.

[0043] Comparative Example 1 Compared with Example 2, this comparative example only omits tetraethyl orthosilicate in the preparation of organosilicon wear-resistant particles and eliminates the corresponding pore confinement treatment; the remaining raw material amounts, preparation steps and process parameters are the same as in Example 2, and will not be repeated here. The final result is a high wear-resistant fluorine-free medical-grade nylon composite material.

[0044] Comparative Example 2 Compared with Example 2, this comparative example only omits OFS-6040 silane in the preparation of organosilicon wear-resistant particles and eliminates the corresponding external surface treatment; the remaining raw material amounts, preparation steps and process parameters are the same as in Example 2, and will not be repeated in this comparative example. Finally, a high wear-resistant fluorine-free medical-grade nylon composite material is obtained.

[0045] Comparative Example 3 Compared with Example 2, this comparative example only omits the flame retardant FCA-117 in the preparation of organosilicon wear-resistant particles; except for the flame retardant FCA-117, the amounts of other raw materials, preparation steps and process parameters are the same as in Example 2, and will not be repeated in this comparative example. Finally, a high wear-resistant fluorine-free medical-grade nylon composite material is obtained.

[0046] Comparative Example 4 Compared with Example 2, this comparative example only changed the spatial addition method of flame retardant FCA-117: flame retardant FCA-117 was not added when preparing organosilicon wear-resistant particles, and flame retardant FCA-117 in the same amount as in Example 2 was added as an independent raw material to the final composite premix; the total amount of other raw materials, preparation steps and process parameters were the same as in Example 2, and finally a high wear-resistant fluorine-free medical-grade nylon composite material was obtained.

[0047] Comparative Example 5 Compared with Example 2, this comparative example only replaces the A1401 wear-resistant agent in the wear-resistant and friction-reducing functional masterbatch with an equal mass of polypropylene; the remaining raw material amounts, preparation steps and process parameters are the same as in Example 2, and will not be repeated in this comparative example. Finally, a high wear-resistant fluorine-free medical-grade nylon composite material is obtained.

[0048] Comparative Example 6 Compared with Example 2, this comparative example only omits the pre-construction of the wear-resistant and friction-reducing functional masterbatch: polypropylene, A1401 wear-resistant agent, maleic anhydride-grafted polypropylene, HPN-68L nucleating agent, and antioxidant 1010 are added as independent raw materials to the final composite premix according to the equivalent amount of the wear-resistant and friction-reducing functional masterbatch in Example 2; the amount of other raw materials, preparation steps, and process parameters are the same as in Example 2, and finally a high wear-resistant fluorine-free medical-grade nylon composite material is obtained.

[0049] The high wear-resistant, fluorine-free medical-grade nylon composite materials prepared in Examples 1-3 and Comparative Examples 1-6 were tested. Standard samples were prepared from the granules of each group using the same injection molding process. The samples were conditioned for 48 hours at 23±2℃ and 50±10% relative humidity before testing. Unless otherwise specified, five parallel samples were set for each test, and the results were taken as the arithmetic mean.

[0050] Dynamic friction coefficient and wear amount: The test was compared with the test method for plastic sliding friction and wear specified in GB / T 3960-2016. The same steel friction pair was used, the test load was 196N, the sliding speed was 0.42m / s, and the test time was 60min. The dynamic friction coefficient in the steady stage was recorded, and the samples were weighed at constant temperature before and after the test to calculate the wear mass.

[0051] Number of grinding debris: The grinding debris in the single friction and wear test area and the collection tank was quantitatively rinsed with isopropanol, filtered with a 10μm polycarbonate filter membrane and dried. The number of particles with a diameter of not less than 10μm was counted under the same microscope magnification and expressed as "particles / test". Each group was tested 3 times and the average value was taken.

[0052] Wipeable material on the surface: The injection-molded flat sample was placed in an environment of 70°C for 7 days. After cooling to room temperature, a fixed area of ​​100 cm² was wiped with isopropanol. The wiping liquid was collected and evaporated to constant weight. After subtracting the blank, the mass of wipeable material per unit area was converted into mg / m². This was used to compare the control effect of different functional structures on the migratable components on the surface.

[0053] Tensile strength: Tested according to the method specified in GB / T 1040.2-2022. All specimens used the same specimen size and tensile speed. Five parallel specimens were tested in each group and the average value was taken.

[0054] Notched impact strength of simply supported beams: tested according to the method specified in GB / T 1043.1-2008. All specimens used the same notch form and specimen size. Five parallel specimens were tested in each group and the average value was taken.

[0055] Table 1. Test results of high wear-resistant, fluorine-free medical-grade nylon composite materials

[0056] As can be seen from the comparison between Example 2 and Comparative Example 1, after simply removing the tetraethyl orthosilicate and the corresponding orifice sealing treatment, the dynamic friction coefficient increased, the wear and debris amount increased significantly, and the surface wipeable material increased significantly. This is because the orifice sealing (the invention description has been modified to orifice confinement; whether the terminology should remain consistent here is for consideration) does not completely seal the organosilicon within the pores, but rather constructs a controllable slow-release channel. During room temperature storage and thermal aging, the inorganic siloxane network at the orifice restricts the free diffusion of organosilicon, thus significantly reducing the surface wipeable material; while during friction, the contact pressure and local high temperature at the friction interface drive the organosilicon within the pores to be slowly and continuously released to the friction interface, forming a stable low-shear lubricating film. After removing the orifice seal, the silicone relies solely on mesoporous adsorption and binding. During thermal aging, a large amount migrates to the material surface, significantly increasing the wipeable surface area. However, during continuous friction, the silicone enriched on the surface is rapidly worn away, resulting in insufficient subsequent lubrication supply. Simultaneously, the unprotected pore structure is prone to collapse, leading to a decrease in the wear resistance of the mesoporous particles themselves. Therefore, the dynamic friction coefficient actually increases in the stable phase, with wear and debris increasing simultaneously. This demonstrates that there is no positive correlation between the dynamic friction coefficient and the wipeable surface area. The wipeable surface area reflects the free migration ability of components, while the dynamic friction coefficient depends on the stability of the continuous lubrication supply at the friction interface.

[0057] A comparison of Example 2 and Comparative Example 2 shows that, by simply removing the OFS-6040 silane surface treatment, the dynamic friction coefficient increased, the wear and debris quantity increased significantly, the tensile strength and notched impact strength decreased markedly, and the surface wipeable material also increased. This indicates that the core function of OFS-6040 silane is to improve the interfacial bonding between the encapsulated particles and the polyamide 12 matrix. After silane treatment, the epoxy groups on the particle surface can react with the terminal amino groups of the polyamide to form a chemically bonded interface, which not only improves the pull-out resistance of the particles but also reduces the interfacial gaps between the particles and the matrix. After removing the surface treatment, the interfacial bonding between the particles and the matrix is ​​weak, and the particles are easily pulled out as a whole during friction, forming third-body abrasive particles. Therefore, the wear and debris quantity increase significantly, and the mechanical properties decrease significantly. At the same time, the interfacial gaps provide channels for the migration of organosilicon, thus increasing the surface wipeable material. The results further confirm that wear is not only affected by interfacial lubrication, but also determined by the interfacial bonding strength between the matrix and the particles. Therefore, systems with similar dynamic friction coefficients may have significant differences in wear.

[0058] A comparison of Example 2 and Comparative Example 3 shows that simply removing the FCA-117 silicone component significantly increases the coefficient of dynamic friction, the amount of wear and debris, while reducing the surface wipeable material. This result clearly distinguishes the two types of performance determinants. FCA-117 silicone is the core lubricating component of the friction interface; its absence directly leads to a significant increase in interfacial shear resistance and a marked deterioration in tribological performance. The main source of surface wipeable material is the migratable silicone component; without silicone, there are no easily migratable low-surface-energy substances in the system, thus reducing the wipeable material to near-pure matrix levels. Therefore, there is no positive correlation between surface wipeable material and tribological performance; they are determined by component migration and interfacial lubrication and interfacial strength, respectively. The design objective of this invention is to achieve a balance between low friction and low precipitation by restricting the free migration of silicone through channel sealing, while ensuring the effective lubrication function of silicone, rather than completely sealing the silicone and rendering it ineffective.

[0059] A comparison of Example 2 and Comparative Example 4 shows that, under the condition of maintaining the same total amount of FCA-117 silicone, simply changing its addition from a channel-impregnated and sealed state to independent and free addition during the final compounding process resulted in an increase in the dynamic friction coefficient, a significant increase in wear and debris quantity, and a substantial increase in surface wipeable material. This single-variable comparison directly proves that the effect of the present invention does not come from the simple superposition of silicone and mesoporous silica, but depends on the restricted slow-release structure formed by channel impregnation and pore sealing. Freely added silicone exists in the matrix as a dispersed phase, unconstrained by pores, thus exhibiting the strongest migration and the highest surface precipitation after thermal aging; however, freely dispersed silicone easily forms a locally enriched phase, which is easily worn away during friction, failing to provide a continuous and stable lubrication supply. Therefore, the dynamic friction coefficient is higher in the stable stage, and the wear and debris quantity also increase significantly. The channel sealing structure controls the release rate of silicone within a reasonable range, ensuring a continuous lubrication supply to the friction interface while avoiding precipitation and rapid depletion caused by free migration.

[0060] A comparison of Example 2 and Comparative Example 5 shows that replacing A1401 wear-resistant agent with an equal mass of polypropylene significantly increased the dynamic friction coefficient, wear amount, and amount of wear debris, while the surface wipeable material level remained close to that of the pure matrix. This indicates that A1401 is the core friction-regulating component in the wear-resistant and friction-reducing masterbatch. As a high-molecular-weight silicone wear-resistant agent with extremely low migration, it does not significantly increase the surface wipeable material. By uniformly distributing in the polyolefin dispersion phase, it continuously improves the shear characteristics of the friction interface, forming a synergistic effect of targeted slow release and overall friction reduction with the silicone wear-resistant particles. These results also further confirm that easily migratable small-molecule and oligomeric silicones are the main source of surface wipeable material, while high-molecular-weight wear-resistant agents have minimal impact on wipeable material.

[0061] Comparing Example 2 and Comparative Example 6, it can be seen that, under the condition that the equivalent amounts of each component raw material remain unchanged, after simply canceling the pre-construction of the wear-resistant and friction-reducing functional masterbatch and adding its component raw materials separately to the final system, the dynamic friction coefficient increases, the wear amount and the amount of wear debris increase significantly, the tensile strength and notched impact strength also decrease, and the surface wipeable material increases. This is because, during the pre-preparation of the functional masterbatch, the A1401 wear-resistant agent, HPN-68L nucleating agent, polypropylene, and maleic anhydride-grafted polypropylene complete pre-dispersion and interfacial composite under high shear, forming a polyolefin functional phase with uniform scale and stable interface; after canceling the pre-construction, the dispersion of each component in the nylon matrix is ​​more random, the polyolefin phase is prone to coarsening, the wear-resistant agent is unevenly distributed, and the interfacial bonding is weak, thus the friction and wear performance decreases, the mechanical properties are also lost, and the local enrichment of components also slightly increases the level of migratable material.

[0062] Based on the results of various comparative examples, the core inventiveness of this invention lies in the controllable, slow-release organosilicon wear-resistant particle structure formed by FCA-117 channel impregnation, tetraethyl orthosilicate orifice sealing, and OFS-6040 external surface treatment, which, together with the pre-constructed wear-resistant and friction-reducing masterbatch, forms a dual-unit synergy. The former solves the contradiction of easy precipitation and depletion of organosilicon lubricating components, while the latter solves the problems of poor dispersion and weak interface of the wear-resistant phase in polyolefins. The combined effect of the two enables the material to simultaneously achieve low friction, low wear, low wear debris, low surface migration, and stable mechanical properties through a simple one-step melt extrusion process, which is different from the modification effect of simple blending.

[0063] The above description is merely an example and illustration of the concept of the present invention. Any modifications, additions, or substitutions made by those skilled in the art to the specific embodiments described, as long as they do not deviate from the concept of the present invention or exceed the scope defined in the claims, shall fall within the protection scope of the present invention.

Claims

1. A high-wear-resistant, fluorine-free medical-grade nylon composite material, characterized in that, The product is composed of the following components by mass: 12,100 parts polyamide, 2.5-5.0 parts silicone wear-resistant particles, 6-12 parts wear-resistant and friction-reducing functional masterbatch, 0.20-0.40 parts antioxidant 1098 and 0.05-0.20 parts antioxidant 168.

2. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 1, characterized in that, The organosilicon wear-resistant particles are prepared by the following method: placing mesoporous silica in a negative pressure environment to expel the gas in the pores; preheating flame retardant FCA-117 to obtain organosilicon impregnation material; adding organosilicon impregnation material to mesoporous silica under negative pressure conditions; and obtaining organosilicon impregnation particles by negative pressure impregnation, restoring normal pressure and mixing. Tetraethyl orthosilicate was added to an aqueous ethanol solution and pre-hydrolyzed to obtain silica sol; organosilicon-impregnated particles were added to the silica sol, and after dispersion, condensation reaction, filtration and drying, pore-confined particles were obtained; OFS-6040 silane was added to an aqueous ethanol solution and pre-hydrolyzed to obtain silane treatment solution; pore-confined particles were added to the silane treatment solution, and after dispersion, heat preservation reaction, filtration, drying and sieving, organosilicon wear-resistant particles were obtained.

3. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 2, characterized in that, The raw materials for the preparation of the organosilicon wear-resistant particles, by mass parts, include: 100 parts mesoporous silica, 8-15 parts flame retardant FCA-117, 4-8 parts tetraethyl orthosilicate, and 2-5 parts OFS-6040 silane.

4. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 2, characterized in that, In the preparation of the organosilicon wear-resistant particles, tetraethyl orthosilicate is pre-hydrolyzed at 25-35℃ for 30-60 min; after the organosilicon impregnated particles are added to silica sol, a condensation reaction is carried out at 40-60℃ for 40-90 min.

5. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 2, characterized in that, During the preparation of the organosilicon wear-resistant particles, OFS-6040 silane is pre-hydrolyzed for 20-40 minutes at a pH of 4.5-5.2; after the pore-confined particles are added to the silane treatment solution, they are kept at 55-70℃ for 60-100 minutes.

6. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 1, characterized in that, The wear-resistant and friction-reducing functional masterbatch is prepared by the following method: polypropylene, A1401 wear-resistant agent, maleic anhydride-grafted polypropylene, HPN-68L nucleating agent and antioxidant 1010 are mixed to obtain masterbatch premix; the masterbatch premix is ​​melt-extruded, cooled and pelletized and dried to obtain wear-resistant and friction-reducing functional masterbatch.

7. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 6, characterized in that, The raw materials for the preparation of the wear-resistant and friction-reducing functional masterbatch include, by mass parts: 100 parts polypropylene, 25-40 parts A1401 wear-resistant agent, 15-25 parts maleic anhydride-grafted polypropylene, 0.20-0.50 parts HPN-68L nucleating agent, and 0.10-0.30 parts antioxidant 1010.

8. The high wear-resistant, fluorine-free medical-grade nylon composite material according to claim 7, characterized in that, The temperature of melt extrusion during the preparation of the wear-resistant and friction-reducing masterbatch is 170-205℃.

9. A method for preparing a high-wear-resistant, fluorine-free medical-grade nylon composite material according to any one of claims 1-8, characterized in that, Polyamide 12, silicone wear-resistant particles, wear-resistant and friction-reducing functional masterbatch, antioxidant 1098 and antioxidant 168 are mixed to obtain a composite premix; the composite premix is ​​melt-extruded, cooled and pelletized and dried to obtain a high wear-resistant fluorine-free medical-grade nylon composite material.

10. The preparation method according to claim 9, characterized in that, The temperature of the melt extrusion of the composite premix is ​​190-230℃.